Development of functional agricultural products utilizing the new health claim labeling system in Japan. Issue 4 (3rd April 2018) - Maeda-Yamamoto, Mari; Ohtani, Toshio
Abstract: In April 2015, Consumer Affairs Agency of Japan launched a new food labeling system known as "Foods with Function Claims (FFC)." Under this system, the food industry independently evaluates scientific evidence on foods and describes their functional properties. As of May 23, 2017, 1023 FFC containing 8 fresh foods have been launched. Meanwhile, to clarify the health-promoting effects of agricultural products, National Agriculture and Food Research Organization (NARO) implemented the "Research Project on Development of Agricultural Products" and demonstrated the risk reduction of osteoporosis of β-cryptoxanthin rich Satsuma mandarins and the anti-allergic effect of the O -methylated catechin rich tea cultivar Benifuuki. These foods were subsequently released as FFC. Moreover, NARO elucidated the health-promoting effects of various functional agricultural products (β-glucan rich barley, β-conglycinin rich soybean, quercetin rich onion, etc.) and a healthy boxed lunch. This review focuses on new food labeling system or research examining functional aspects of agricultural products. Abstract : :